The Problems of Prime Cost Formation Accounting In Poultry Farm Incubators - Alevtina Vasilievna KOROTKOVA; Larisa Vitalyevna BAKULEVSKAYA; Evgeniy Alekseevich IVANOV; Nadezhda Leonidovna DANILOVA; G. M. TOBOEV; Andrey Evgenievich MAKUSHEV (Communications of International Proceedings, 2021)
This study develops the theory of prime cost formation accounting in poultry farm incubators. It connects the process of cost accounting and prime cost formation6, justifies various methods of prime cost accounting and formation in incubators and their interconnection, discusses problems on these issues, develops and provides recommendations for eliminating the problems of prime cost accounting in incubators.
Keywords: prime cost of finished products; estimating; farming; cost accounting; poultry farming; accounting problems